A Panel Data Toolbox for MATLAB - Inmaculada C. Álvarez; Javier Barbero; José L. Zofío (Journal of Statistical Software, 2017)
Panel Data Toolbox is a new package for MATLAB that includes functions to estimate the main econometric methods of balanced and unbalanced panel data analysis. The package includes code for the standard fixed, between and random effects estimation methods, as well as for the existing instrumental panels and a wide array of spatial panels. A full set of relevant tests is also included. This paper describes the methodology and implementation of the functions and illustrates their use with well-known examples. We perform numerical checks against other popular commercial and free software to show the validity of the results.